Barriers of new technology introduction and disadvantages of Industry 4.0 for industrial enterprises - Pech, Martin; Vaněček, Drahoš (Serbian Journal of Management, 2022)
The rise of new technologies known as the fourth industrial revolution (Industry 4.0), brings a transformation that makes it possible to produce and manufacture products on machines through robots in modern smart factories. Industry 4.0 will increase productivity, quality of goods, foster industrial growth, and modify the profile of the workforce and required competences. However, such benefits and advantages should be assessed in light of potential barriers and negative consequences. The paper deals with the barriers of new technology introduction and main disadvantages of Industry 4.0. Based on questionnaire research in 217 industrial enterprises, the differences between enterprises according to their size and technological intensity are analysed. The main barriers of technology introduction and Industry 4.0 disadvantages are lack of funds, high costs, production process optimization and high investment need. The research confirmed only small differences in managers’ preferences of Industry 4.0 technology barriers and Industry 4.0 disadvantages according to the enterprise size. The technological intensity was important only partly in case of perception of Industry 4.0 disadvantages. The key contributions of this work are promising results for a better understanding of technology barriers and Industry 4.0 disadvantages.
Keywords: Industry 4.0; technology barriers; disadvantages; technological intensity